Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan di SMPK Mardi Wiyata Kediri - Wijna Jagadhita; Rike Kusuma Wardhani; Angga Permana Mahaputra (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the simultaneous and partial influence of leadership style and work discipline on employee performance. This type of quantitative research, this research uses primary and secondary data. The research sample consisted of 35 employees of SMPK Mardi Wiyata Kediri using saturated sampling techniques. The analysis techniques used were validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, t test, F test, multiple linear regression analysis, and test the coefficient of determination (R2) using the SPSS version 25 program.The research results show that the t test results of the Leadership Style variable (X1) have a partially significant effect on Employee Performance by getting a sig value. 0.001 < 0.05 and the Work Discipline variable (X2) has a partially significant effect on Employee Performance with a sig. 0.004 < 0.05. Meanwhile, the results of the F test show that Leadership Style (X1) and Work Discipline (X2) have a significant simultaneous effect on Employee Performance at SMPK Mardi Wiyata Kediri with a sig. 0.000 < 0.05. In this research, it is also known that the coefficient of determination (R2) Adjusted R square variable Leadership Style and Work Discipline has an influence of 60.5% in influencing employee performance, while the remaining 39.3% is influenced by other variables not discussed in this research.